Respuesta :
Answer:
The answer to your question is below
Step-by-step explanation:
C (-4, 3)
V (-4, 7)
asymptotes = 2 = [tex]\frac{b}{a}[/tex]
- This is a vertical hyperbola, the equation is
[tex]\frac{(y - k)^{2} }{a^{2} } + \frac{(x - h)^{2} }{b^{2} } = 1[/tex]
slope = 2
a is the distance from the center to the vertex = 4
b = 2(4) = 8
[tex]\frac{(y - 3)^{2} }{4^{2} } + \frac{(x + 4)^{2} }{8^{2} } = 1[/tex]
[tex]\frac{(y - 3)^{2} }{16} + \frac{(x + 4)^{2} }{64} = 1[/tex]
Answer:
[tex]\frac{(x+4)^{2}}{4} - \frac{(y-3)^{2}}{16} = 1[/tex]
Step-by-step explanation:
The hyperbola centered at (h,k) has the following expression:
[tex]\frac{(x-h)^{2}}{a^{2}} - \frac{(y-k)^{2}}{b^{2}} = 1[/tex]
Where [tex]a[/tex] and [tex]b[/tex] are the length of the horizontal and vertical semi-axes, respectively.
Since the center and one vertex share the same vertical component ([tex]x=-4[/tex]), it is easy to conclude that hyperbola has a vertical configuration ([tex]b > a[/tex]). The distance between the center and the known vertex is equal to the length of the vertical semi-axis. Therefore:
[tex]b = 4[/tex]
The slope of the hyperbola is given by the following relationship:
[tex]\frac{b}{a} = 2[/tex]
The length of the horizontal semi-axis is:
[tex]a = \frac{b}{2}[/tex]
[tex]a = 2[/tex]
The standard form of the equation of the hyperbola is:
[tex]\frac{(x+4)^{2}}{4} - \frac{(y-3)^{2}}{16} = 1[/tex]